Trace fossils from the Lower–Middle Jurassic Bardas Blancas Formation, Neuquén Basin, Mendoza Province, Argentina - Bressan, Graciela Susana (2009)
Trace fossil associations from the Lower–Middle Jurassic siliciclastic succession of the northern Neuquén Basin, Argentina are described and their palaeoenvironmental interpretation is discussed. The Bardas Blancas Formation displays facies of lower foreshore to offshore environments, such as massive and laminated mudstones, laminated siltstones, hummocky cross-stratified sandstones, massive and laminated sandstones, wave-rippled sandstones, as well as fine- to medium-grained bioclastic sandstones and massive conglomerates. They contain a tracefossil assemblage low in abundance but high in diversity. The assemblage, comprising eleven ichnogenera, is dominated by Skolithos, Chondrites, Thalassinoides, Planolites, Palaeophycus, Taenidium, Gyrochorte and Arenicolites.Gordia, ?Diplocraterion and Lockeia are less abundant. These trace fossils belong to the Skolithos, Cruziana and Zoophycos ichnofacies. Their distribution is controlled mainly by hydrodynamic energy, substrate consistency and oxygen levels. Storm beds exhibit two successive stages of colonization: (1) the pioneer stage, during which Skolithos, Diplocraterion and Arenicolites (elements of the Skolithos ichnofacies), were produced; and (2) the stable environment stage, represented by Chondrites, Thalassinoides, Taenidium, Gyrochorte, Gordia, Lockeia, Palaeophycus and Planolites (elements of the Cruziana ichnofacies). deeper environments exhibit a low diversity association with Chondrites and Thalassinoides, characterizing the Zoophycos ichnofacies. Trace fossils; ichnotaxonomy; ichnofacies; Neuquén Basin; Jurassic; Argentina. Acta Geologica Polonica, Vol. 59 (2009), No. 2, pp. 201–220 abstracts (Bressan and Palma 2007; Bressan and Palma 2008. The aims of this paper are to document the trace fossils from the Lower–Middle Jurassic siliciclastic stormdominated marine platform of the Neuquén Basin, which is exe